Impact of COVID-19 on education sector in Uttarakhand: Exploratory factor analysis - Gupta, Neema; Sharma, Megha; Rastogi, Mohit; Chauhan, Anshu; Jain, Vipin; Yadav, Piyush Kumar (Linguistics and Culture Review, 2021)
COVID-19 pandemic has adversely impacted the whole education system across the world. Approximately 2 billion students have been impacted due to the closures of school, colleges and universities in the context to corona virus pandemic at the mid of May 2020. In context to the problems due to COVID-19 pandemic, experienced by the people, having close association with the education sector, the research is conducted to determine the impact of COVID-19 on education sector in Uttarakhand. Collection of data was done with the help of self structured questionnaire and it was distributed to 186 respondents of colleges and universities of Uttarakhand. Questionnaire was prepared in a Google-form. Collection of data was done with the help of convenience sampling method. In order to extract the factors from my study ie. “Impact of COVID-19 pandemic on education sector in Uttarakhand”, exploratory factor analysis is used. Data analysis is done with the help of SPSS and Microsoft Excel.The extracted factors in this study were Rise in unemployment, Online learning will act as a critical lifeline for education Salary, payment to the employees irrespective of their capability, Lack of technological knowledge to access the online learning method, Requirement of technically sound system.